Job Satisfaction Analysis of Nurses Using Science and Cano Integration - Johan Budhiana; Rosliana Dewi; Syiva Dwi Fatmala (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aim: Important success elements for health care include nursing services. The best possible nurse job satisfaction is required since nurses play a significant role in patient care. The goal of the study was to evaluate nurses' job satisfaction at Jampangkulon General Hospital in the West Java Province by combining the IPA and KANO techniques. Methods: Research of this kind is descriptive. A sample of 120 nurses from the population of nurses in the inpatient room at Jampangkulon General Hospital in the West Java Province. employing the proportional random sampling method for sampling. The Minnesota Satisfaction Questionnaire was the research tool that was employed. A questionnaire was utilized for data collecting. Results: The average value of the importance level was 3.60, the average value of the performance level was 3.51, the average value of the gap level was -0.09, the CSI value was 0.70, and based on the IPA-KANO integration, it showed three priorities: performing work following one's profession as a nurse; receiving compensation commensurate with one's work; and working in conducive conditions (temperature, lighting, air circulation, and cleanliness) where one can perform one's duties. Conclusion: The results highlight key performance metrics, including working in line with one's profession as a nurse and being paid appropriately for the work performed. It is intended that the Jampangkulon General Hospital in the West Java Province will periodically survey employees to gauge their level of job satisfaction.